Cancer systems biology - Wang, Edwin (Chapman & Hall/CRC mathematical and computational biology series, 2010)
The unprecedented amount of data produced with high-throughput experimentation forces biologists to employ mathematical representation and computation to glean meaningful information in systems-level biology. This book introduces the concepts and theories of systems biology and the applications of systems biology in cancer research